2008
DOI: 10.4028/www.scientific.net/kem.375-376.216
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Diamond Spherical Shell Thick Film by DC Plasma CVD

Abstract: Diamond spherical shell thick film was prepared by high power DC-plasma jet CVD. Atom force microscopy, scanning electron microscopy, Raman spectroscopy and roughness-profile-meter were used to characterize microstructure, morphology, impurities and orientation evolution of diamond spherical shell thick film. The results show that, when nucleation begins, grains grow random orientation. The grain size of spherical diamond film prepared is compact, clear, uniform, continuous and no remarkable bigger grain over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…We will develop a new way of DC plasma jet CVD way to synthesis the cBN film. Our team has prepared thick diamond film with DC plasma jet CVD apparatus (figure 2) for many years [22] . The nontransferable plasma torch has a cylindrical anode and a cathode rod and the anode nozzle's diameter is between 1 and 3 mm.…”
Section: Technological Bottlenecks Of Cbn Films Prepared By DC Plasma...mentioning
confidence: 99%
See 2 more Smart Citations
“…We will develop a new way of DC plasma jet CVD way to synthesis the cBN film. Our team has prepared thick diamond film with DC plasma jet CVD apparatus (figure 2) for many years [22] . The nontransferable plasma torch has a cylindrical anode and a cathode rod and the anode nozzle's diameter is between 1 and 3 mm.…”
Section: Technological Bottlenecks Of Cbn Films Prepared By DC Plasma...mentioning
confidence: 99%
“…The holder can be DC biased. The substrate's temperature is measured by infra-red temperature tester [22] . The experimental conditions fore the deposition of the cBN film are listed in table 3.…”
Section: Technological Bottlenecks Of Cbn Films Prepared By DC Plasma...mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, small spherical materials have been widely applied in many industrial fields, such as semiconductors, tribology and advanced catalysts [7][8][9]. Generally, the CVD diamond had a columnar shape with {111} crystalline face after a deposition time of several hours, while the spherical diamond grains commonly appeared at the initial stage of CVD deposition and only discretely distributed on the substrate surface at nanometric scale size [10]. Hence, it was significant to research the deposition process of large spherical diamond for the tribological applications of CVD diamond [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Inevitably, the impurities of ferrous metal (Fe, Ni and Cr) would be introduced and consequently decreased the quality of products. Recently, Li et al [5,6] reported the synthesis of opaque spherical shell-shaped diamond films deposited on molybdenum (Mo) by dc-plasma jet CVD. As an important and effective deposition method, microwave plasma CVD (MPCVD) has been widely used to fabricate optical grade diamond films.…”
mentioning
confidence: 99%